Experimental acid and scCO2 reactions of Roseneath, Epsilon and Murteree gas shales: Opening or closing of gas accessible pores and metal release to water. Issue 1 (1st December 2019) - Pearce, J. K.; Blach, T.; Dawson, G.; Melnichenko, Y.; Southam, G.; Golding, S.D.; Bahadur, J.; Paterson, D.
Summary: Shale oil and gas is of recent interest in Australia, and the Roseneath, Epsilon and Murteree (REM) shales of the Cooper Basin, Australia, are unconventional gas targets. Shales have a high proportion of porosity in the submicron scale and hydraulic stimulation of USA shales has historically employed high volumes of water with dilute HCl, proppants and various chemicals. Supercritical (sc) CO2 has also been used as a fracture fluid in water sensitive formations. In addition, shales may contain high concentrations of potentially toxic or regulated components such as U, As, Pb, or BTEX which may be released to production water. Improper disposal or treatment of waste water has caused recent environmental concerns in the USA. REM shales were characterised with various techniques including high resolution synchrotron XFM for association of metals with specific minerals. Several metals and As were associated with sulphides in coal pores; Mn with siderite, and Pb with pyrite cements. Shales were reacted with dilute HCl or scCO2 -water +/- SO2 . The fraction of SANS gas accessible meso-pores was highest in the Epsilon Formation core. Siderite dissolved in HCl reactions, and the fraction of open meso-pores increased. Fe-rich precipitates formed in scCO2 reactions and mesopores partly closed. Mobilised concentrations of Pb, Fe, U, and Na were highest from the reactions with dilute HCl. Understanding the mineral sources of metals and their potential release with different fracture fluids may result in better predictions and mitigation options for production water. Reactions of minerals such as siderite, and sulphides may release regulated metals to production water.